2017
DOI: 10.1002/lio2.44
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modelling of Cough Function and Airway Penetrant Behavior in Patients with Disorders of Laryngeal Function

Abstract: Objective/HypothesisPatients with laryngeal disorders often exhibit changes to cough function contributing to aspiration episodes. Two primary cough variables (peak cough flow: PCF and compression phase duration: CPD) were examined within a biomechanical model to determine their impact on characteristics that impact airway compromise.Study DesignComputational studyMethodsA Computational Fluid Dynamics (CFD) technique was used to simulate fluid flow within an upper airway model reconstructed from patient CT ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…One of the most important and least understood aspects of turbulence is when the local Reynolds number of the turbulence is relatively low [1]. Effects of turbulence is of interest in various industrial [2][3][4][5][6] and biomedical [7][8][9][10][11] applications. Most fluid flows are characterized by irregularly fluctuating flow quantities that often occur at small scales and high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important and least understood aspects of turbulence is when the local Reynolds number of the turbulence is relatively low [1]. Effects of turbulence is of interest in various industrial [2][3][4][5][6] and biomedical [7][8][9][10][11] applications. Most fluid flows are characterized by irregularly fluctuating flow quantities that often occur at small scales and high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Coughing is an important human defense reflex that protects the respiratory system from infections and improves the clearance of secretions [1][2][3][4]. It is usually caused by inflammation and respiratory infections of the respiratory airways or larynx.…”
Section: Introductionmentioning
confidence: 99%
“…50,51 Duration of the cough compression phase has been suggested to primarily manipulate the pace of cough (fast/slow), whereas CPF affects the power of cough (strong/weak). 52 The threshold for clinically effective secretion removal has been proposed at CPF of 160-180 l/min. 6,[53][54][55][56] CPF constitutes the most commonly used measure to determine the effect of spontaneous or assisted cough in persons with NMDs.…”
Section: Cough Is Not a Cough Without A Functioning Larynxmentioning
confidence: 99%
“…86 Lachal et al 87 enhance our understanding of airflow dynamics, and a wide range of MI-E settings may be systematically applied to suggest possible combinations to be applied subsequently in patients. 52,88 The dogma that upper airway collapse during exsufflation causes MI-E treatment failure, highly influenced former evaluation methods, assessing the exsufflation phase alone. Sancho et al's CT-scannings 25 and Lacombe's flow-curve shapes 84 confirmed Bach's postulate that exsufflation caused upper airway collapse in subjects with bulbar dysfunction.…”
Section: Laryngeal Modelsmentioning
confidence: 99%